Recruiting and consenting into a peripartum trial in an emergency setting: a qualitative study of the experiences and views of women and healthcare professionals - Hallowell, N; Lawton, J; Snowdon, C; Morrow, S; Norman, J; Denison, F (BioMed Central, 2016)
Background Recruiting and consenting women to peripartum trials can be challenging as the women concerned may be anxious, in pain, and exhausted; there may also be limited time for discussion and decision-making to occur. To address these potential difficulties, we undertook a qualitative evaluation of the internal pilot of a trial (Got-it) involving women who had a retained placenta (RP). We explored the experiences and views of women and staff about the information and consent pathway used within the pilot, in order to provide recommendations for use in future peripartum trials involving recruitment in emergency situations. Methods In-depth interviews were undertaken with staff (n= 27) and participating women (n= 22). Interviews were analysed thematically. The accounts of women and staff were compared to identify differences and similarities in their views about recruitment and consent procedures. Results Women and staff regarded recruitment as having been straightforward and facilitated by the use of simplified (verbal and written) summaries of trial information. Both parties, however, conveyed discordant views about whether fully informed consent had been obtained. These differences in perspectives appeared to arise from the different factors and considerations impinging on women and staff at the time of recruitment. While staff placed emphasis on promoting understanding in the emergency situation of RP by imparting information in clear and succinct ways, women highlighted the experiential realities of their pre- and post-birthing situations, and how these had led to quick decisions being made without full engagement with the potential risks of trial participation. To facilitate informed consent, women suggested that trial information should be given during the antenatalperiod,and,indoingso,articulatedarights-based discourse. Staff, however, voiced opposition to this approach by emphasising a duty of care to all pregnant women, and raising concerns about causing undue distress to the majority of individuals who would not subsequently develop a RP. Conclusions By drawing upon the perspectives of women and staff involved in the same trial we have shown that they may operate within different experiential and ethical paradigms. In doing so, we argue for the potential benefits of drawing upon multiple perspectives when developing information and consent pathways used in future (peripartum) trials.